The imagined and real Jerusalem in art and architecture - Goudeau, Jeroen; Verhoeven, Mariëtte, 1963-; Weijers, Wouter (Radboud studies in humanities, 2014)
In 'The imagined and real Jerusalem in art and architecture' specialists in various fields of art history, from Early Christian times to the present, articulate a variety of cultural, religious and political implications of the visualization of Jerusalem. This collection of essays calls attention to two axes emerging from the study of Jerusalem in art: on the one hand, the volatile contemporary situation, and on the other hand, the abiding chain of meanings that history imparts to the city. From a contemporary perspective and within a broad historical context, the book discusses in depth a series of Western artworks, artefacts, and buildings providing new insights into memory processes and mechanisms of representation of Jerusalem.